MODEL OF FORMATION OF READINESS OF THE TEACHER FOR WORK WITH THE CHILDREN WHO SHOWED OUTSTANDING ABILITIES - A. Volkov; O. Chursinova; A. Yaroshuk (Вестник Северо-Кавказского федерального университета)
In this article the analysis of the main structural components of readiness of the teacher for work with the children who showed outstanding abilities is given, the main professional and important qualities necessary for effective work with exceptional children are analyzed (communicative, perceptual, etc.). The model of formation ofreadiness of the teacher for work with the children who showed outstanding abilities is also developed and described, methods of diagnostics of the main structural components of readiness of the teacher for work with children of this category are listed. The role of a system of professional development and self-education in development and improvement of a pedagogical reflection, communicative competence, increase in motivation to work with exceptional children is shown.